Floodplain modeling using HEC-RAS - Haestad (HAESTAD Press, 1900)
If your work or academic studies involve floodplain management, then a copy of Floodplain Modeling Using HEC-RAS needs to be on your desk. This comprehensive textbook offers expert instruction and practical advice for floodplain modelers and managers. It then goes a step further and shows readers how to apply HEC-RAS, the worldwide standard simulation tool from the U.S. Army Corps of Engineers.